THE CONSTRUCTION OF THE PEDAGOGICAL AUTHORITY NOTION FROM THE PERSPECTIVE OF INSERVICE TEACHERS - Parra, Jeannette (2022)
When talking about authority in any field, it mostly relates to respect, discipline and order. The objective of this study is to analyze the construction of pedagogical authority, with a focus on gender from the perspective of in-service elementary school teachers. Under the scope of the qualitative research methodology of case study, two focus groups were conducted on in-service teachers from a school in Chile. The analysis plan contemplated open coding with the aim of breaking down the empirical corpus into units of meaning that were categorized to obtain a hierarchical code map. The findings revealed three main categories: a) the different understandings of authority, b) in-service teacher’s experiences and c) authority models perceived as positive and negative. These categories were further systematized into the corresponding subcategories, interpreted through theoretical triangulation and source analysis. The results indicated that the participants agree that it is during the pedagogical practice where they learn more about pedagogical authority. In addition, differences were identified between the pedagogical styles of teachers due to their gender characteristics that would affect their behaviors with the students.